Magnetic and elastic anisotropy in magnetorheological elastomers using nickel-based nanoparticles and nanochains - Landa, Romina Ailín (2013)
Nickel (Ni) based nanoparticles and nanochains were incorporated as fillers in polydimethylsiloxane (PDMS) elastomers and then these mixtures were thermally cured in the presence of a uniform magnetic field. In this way, macroscopically structured-anisotropic PDMS-Ni based magnetorheological composites were obtained with the formation of pseudo-chains-like structures (referred as needles) oriented in the direction of the applied magnetic field when curing. Nanoparticles were synthesized at room temperature, under air ambient atmosphere (open air, atmospheric pressure) and then calcined at 400 °C (in air atmosphere also). The size distribution was obtained by fitting SAXS experiments with a polydisperse hard spheres model and a Schulz-Zimm distribution, obtaining a size distribution centered at (10.0 - 0.6) nm with polydispersivity given by sigma= (8.0 ± 0.2) nm. The SAXS, XRD and TEM experiments are consistent with single crystal nanoparticles of spherical shape (average particle diameter obtained by TEM: (12 ± 1) nm). Nickel-based nanochains (average diameter: 360 nm; average length: 3 mm, obtained by SEM; aspect ratio=length/diameter ~10) were obtained at 85 ºC and ambient atmosphere (open air, atmospheric pressure). The magnetic properties of Ni-based nanoparticles and nanochains at room temperature are compared and discussed in terms of surface and size effects. Both Ni-based nanoparticles and nanochains were used as fillers for obtaining the PDMS structured magnetorheological composites, observing the presence of oriented needles. Magnetization curves, ferromagnetic resonance spectra (FMR) and strain-stress curves of low filler´s loading composites (2% w/w of fillers) were determined as functions of the relative orientation respect to the needles. The results indicate that even at low loadings it is possible to obtain magnetorheological composites with anisotropic properties, with larger anisotropy when using nanochains. For instance, the magnetic remanence, the FMR-resonance field and the elastic response to compression are higher when measured parallel to the needles (about 30% with nanochains as fillers). Analogously, the elastic response is also anisotropic, with larger anisotropy when using nanochains as fillers. Therefore, all experiments performed confirm the high potential of nickel nanochains to induce anisotropic effects in magnetorheological materials.